ANALISIS POSITIONING COFFEE SHOP LOKAL DI WILAYAH JABODETABEK - Annysa Alifia Putri; Sri Vandayuli Riorini (STMIK Widuri Jakarta, 2024)
This research aims to examine the concept of coffee shop brand positioning in Indonesia, namely Kopi Janji Jiwa, Kopi Kenangan, Point Coffee, Kopi Lain Hati, and Kopi Kulo. The data collection method used was by distributing questionnaires online with samples taken using non-probability sampling techniques with purposive sampling to respondents who enjoy 5 coffee shop brands in Indonesia. Descriptive testing is used to analyze the influence of positioning on the coffee shop brand. The data used in this research is primary data obtained from distributing questionnaires to 41 respondents. This research uses cross sectional research, namely a research method carried out over a relatively short time and in a certain place. The data analysis method used in this research is to analyze the attributes owned using the attribute based approach. In this research, three outputs will be produced, namely canonical discriminant function, preference map, as well as market strategy and marketing mix.